2009
DOI: 10.1038/sj.bjc.6605478
|View full text |Cite
|
Sign up to set email alerts
|

PSMB7 is associated with anthracycline resistance and is a prognostic biomarker in breast cancer

Abstract: BACKGROUND: To date individual markers have failed to correctly predict resistance against anticancer agents in breast cancer. We used gene expression patterns attributable to chemotherapy-resistant cells to detect potential new biomarkers related to anthracycline resistance. One of the genes, PSMB7, was selected for further functional studies and clinical validation. METHODS: We contrasted the expression profiles of four pairs of different human tumour cell lines and of their counterparts resistant to doxorub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…LHX2 is a TF involved in the differentiation of developing lymphoid and neural cell precursors and is a putative oncogene for pancreatic tumors (Zhou et al, 2014). PSMB7 is a proteasome subunit that was identified as a biomarker for breast and colon cancers (Munkácsy et al , 2010). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LHX2 is a TF involved in the differentiation of developing lymphoid and neural cell precursors and is a putative oncogene for pancreatic tumors (Zhou et al, 2014). PSMB7 is a proteasome subunit that was identified as a biomarker for breast and colon cancers (Munkácsy et al , 2010). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Smith et al (2007) reported that the over-expression of the PSMB1 proteasomal subunit is associated with resistance to cisplatin in cancer cell lines [44]. Furthermore, PSMB7 has been proved to be associated with anthracycline-resistance in breast cancer [45]. Overexpression of the POH1 subunit confers resistance to vinblastine, cisplatin, doxorubicin and paclitaxel in mammalian cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, because BD and IP genes represent sustained and transient drug-induced changes, respectively, their overlaps may still be irrelevant to drug resistance. Munkácsy et al proposed that IP genes should be excluded from BD genes [ 18 ]. However, some IP genes could be drug resistance genes, and it is difficult to determine which IP genes should be excluded.…”
Section: Introductionmentioning
confidence: 99%